Antimicrobial and anthelmintic activities of aryl urea agents - de Resende, Pedro Ernesto; Nisler, Jaroslav; Voller, Jiří; Kadlecová, Alena; Gibbons, Simon (Journal of global antimicrobial resistance (Print), 2023)
OBJECTIVES: This study aimed to characterise compounds with activity against carbapenemase-expressing Gram-negative bacteria and nematodes and evaluate their cytotoxicity to non-cancerous human cells. METHODS: The antimicrobial activity and toxicity of a series of phenyl-substituted urea derivatives were evaluated using broth microdilution, chitinase, and resazurin reduction assays. RESULTS: The effects of different substitutions present on the nitrogen atoms of the urea backbone were investigated. Several compounds were active against Staphylococcus aureus and Escherichia coli control strains. Specifically, derivatives 7b, 11b, and 67d exhibited antimicrobial activity against Klebsiella pneumoniae 16, a carbapenemase-producing Enterobacteriaceae species, with minimum inhibitory concentration (MIC) values of 100, 50, and 72 μM (32, 64, and 32 mg/L), respectively. In addition, the MICs obtained against a multidrug-resistant E. coli strain were 100, 50, and 36 μM (32, 16, and 16 mg/L) for the same compounds, respectively. Furthermore, the urea derivatives 18b, 29b, 50c, 51c, 52c, 55c-59c, and 62c were very active towards the nematode Caenorhabditis elegans. CONCLUSIONS: Testing on non-cancerous human cell lines suggested that some of the compounds have the potential to affect bacteria, especially helminths, with limited cytotoxicity to humans. Given the simplicity of synthesis for this class of compounds and their potency against Gram-negative, carbapenemase-expressing K. pneumoniae, aryl ureas possessing the 3,5-dichloro-phenyl group certainly warrant further investigation to exploit their selectivity.
Keywords: Anti-Infective Agents; Humans; Bacteria; Anthelmintics; Escherichia coli; antibakteriální látky; Anti-Bacterial Agents; antiinfekční látky; anthelmintika; lidé